Competition policy in the EEC - Ingo Schmidt (Intereconomics, 1973)
Article 2 of the Treaty of Rome describes the task of the European Community as to encourage stability and growth “by establishing a Common Market and by progressively approximating the economic policies of Member States”.
Keywords: 330; Common Market